MARKETING CAMPAIGNS FOCUSED ON THE INTERNATIONAL MARKET: ADAPTATION AND LOCALIZATION - Mamatkulova Shoira Jalolovna (Web of Journals Publishing, 2024)
The article examines key aspects of adapting and localizing marketing campaigns for successful entry into international markets. It emphasizes the importance of taking into account the cultural, linguistic and social characteristics of the target audience to improve the effectiveness of marketing strategies. It describes methods for studying international markets and offers tools that allow companies to adapt their messages, products and advertising materials in accordance with local preferences. The recommendations presented will help businesses strengthen their position and increase their competitiveness at the global level.
Keywords: marketing campaigns, international market, adaptation, localization, cultural differences, target audience, globalization, brand, competitiveness, marketing strategy.